Dual oncogenic role of RNF220 in AML: linking metabolic rewiring to cell proliferation and immune evasion - Li, Bixia; Jiang, Shi; Xu, Yao; Yan, Xiao; Mu, Qitian; Ouyang, Guifang (Frontiers in Oncology, 2025)
BackgroundAcute myeloid leukemia (AML) remains a clinical challenge with suboptimal long-term survival. While circular RNAs derived from the RNF220 host gene have been implicated in AML pathogenesis, the functional role and regulatory mechanisms of RNF220 itself in AML are poorly understood.MethodsWe integrated bioinformatics analyses of public databases (TCGA-LAML, TARGET-LAML) and local cohort with in vitro functional assays. RNF220 was knocked down and overexpressed in AML cell lines using lentivirus. Transcriptomic profiling (RNA-seq), metabolic pathway enrichment (GSVA, GSEA), and immune microenvironment deconvolution (xCELL, CIBERSORT, MCP-counter) were performed. Transcription factor binding sites were predicted across five databases (JASPAR, ENCODE, GTRD, etc.). Validation of transcriptional regulation was performed using ChIP-PCR and luciferase reporter assays.ResultsRNF220 overexpression correlated with poor prognosis in AML, drove an immunosuppressive microenvironment characterized by reduced CD8+ T cells, and inhibited NK activity and M2 polarization of macrophage. RNF220 promoted tumor proliferation by suppressing apoptosis and preventing G1 arrest. Knockdown of RNF220 dysregulated metabolic pathways, notably suppressing glycolysis and phenylalanine metabolism. Mechanistically, FOXA1 was identified as an upstream negative regulator of RNF220, where high FOXA1 predicted favorable survival and inversely correlated with RNF220-associated metabolic reprogramming.ConclusionNF220 acts as an oncogenic ubiquitin ligase in AML by coordinating dual pro-leukemic mechanisms: cell-intrinsic metabolic rewiring (glycolysis/phenylalanine) and immune evasion via microenvironment suppression. Targeting the FOXA1–RNF220 axis may offer novel therapeutic strategies for high-risk AML.